Human Interaction with Creators and Fellow Creatures (Study of Communication Relations of XYZ in Alamin Theory) - Muhammad Aminullah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
These studies are important to understand the process of interaction in human relations with the creator and also relationships with fellow creatures. The research method used is a qualitative research based on content analysis approach, with the aim to be able to explore the theory of alamin used in this study. The results found that interaction was formed by the existence of one of the most basic objectives in communication, namely necessity. This concept can be understood that everything needed by humans, then must have a process of relationships in the form of interaction to be able to achieve whatever objects are needed. But the interaction process is different. Therefore human interactions have two goals. First, human interaction with the creator called the relationship X with Y. This interaction is carried out by X to Y in the form of a relationship as creator to X, provider of living facilities to X, trustee Y, and X servant Y. Second is human interaction with the universe this is called the relationship X with Z. This interaction is carried out by X to Z in the form of a Z relationship as a reference for X, a provider of mass space for X, a power provider for X, and a proof of space for the implementation of the X assignment.